On the Probabilities of Correlated Defaults: a First Passage Time Approach - Valužis, M. (Nonlinear Analysis: Modelling and Control, 2008)
This article investigates the joint probability of correlated defaults in the first passage time approach of credit risk subject to condition that the underlying firms’ assets values and the default boundaries follow geometric Brownian motion processes. The exact analytical expression of joint probability of two correlated defaults in the case of stochastic default boundaries is presented. Also, some properties of this solution are provided.